The changing role of an examination board: a case study of Hong Kong - Lo, Margaret Wai Ki (2013)
This case study examines the changing role of the Hong Kong Examinations and Assessment Authority with a view to identifying the way forward for it to enhance its effectiveness and inform future assessment development. The research questions are: